Designing An Education & Training Management (DIKLAT) Application for Web-Based ASN Needs in The Directorate General Of Marine Transportation Environment - Kurniawan, Asep Rizal; Zulhalim, Zulhalim; Sianipar, Anton Zulkarnain; Yasin, Verdi (Jurnal Teknologi Informatika dan Komputer, 2025)
The Directorate General of Sea Transportation (DJPL) is under and responsible to the Minister of Transportation and is led by the Director General. The Directorate General of Sea Transportation has the task of carrying out the formulation and implementation of policies in the shipping sector. To create a more effective and efficient organization and work procedures to improve the performance of the duties and functions of the Directorate General of Sea Transportation (DJPL), optimal human resource management is needed. The use of information technology has now become mandatory in managing human resources in the government sector. Currently, data processing for education, training and careers within the Secretariat of the Directorate General of Sea Transportation still uses manual methods, causing several obstacles, including irregular data archiving which makes it difficult to search for data as a reference for building a management information system that can provide information regarding management activities within the Directorate General of Sea Transportation. The Technical Implementation Unit (UPT) within the Secretariat of the Directorate General of Sea Transportation, is one of the sections tasked with providing training for employees. Employees who have completed training are then placed according to the results of the training. The Web-Based Information System Design Application for the Technical Implementation Unit (UPT) of the Secretariat of the Directorate General of Sea Transportation (SETDITJEN) was designed using a PHP program and a database using MySQL, so that it can be easily accessed anywhere.